Mandatory IFRS Adoption and Financial Statement Comparability - Brochet, Francois; Jagolinzer, Alan D.; Riedl, Edward J. (Contemporary Accounting Research, 2013)
This study examines whether mandatory adoption of International Financial Reporting Standards ( IFRS ) leads to capital market benefits through enhanced financial statement comparability. U.K. domestic standards are considered very similar to IFRS , suggesting any capital market benefits observed for U.K.‐domiciled firms are more likely attributable to improvements in comparability (i.e., better precision of across ‐firm information) than to changes in information quality specific to the firm (i.e., core information quality). If IFRS adoption improves financial statement comparability, we predict this should reduce insiders' ability to benefit from private information. Consistent with these expectations, we find that abnormal returns to insider purchases ― used to proxy for private information ― are reduced following IFRS adoption. Similar results obtain across numerous subsamples and proxies used to isolate IFRS effects attributable to comparability. Together, the findings are consistent with mandatory IFRS adoption improving comparability and thus leading to capital market benefits by reducing insiders' ability to exploit private information.